Promoting Adherence to Influenza Vaccination Recommendations in Pediatric Practice - Lloyd N. Werk MD, MPH (Journal of Primary Care & Community Health, 2019)
Objectives: In the United States, nonadherence to seasonal influenza vaccination guidelines for children and adolescents is common and results in unnecessary morbidity and mortality. We conducted a quality improvement project to improve vaccination rates and test effects of 2 interventions on vaccination guidelines adherence. Methods: We conducted a cluster randomized control trial with 11 primary care practices (PRACTICE) that provided care for 11 293 individual children and adolescents in a children’s health care system from September 2015 through April 2016. Practice sites (with their clinicians) were randomly assigned to 4 arms (no intervention [Control], computerized clinical decision support system [CCDSS], web-based training [WBT], or CCDSS and WBT [BOTH]). Results: During the study, 55.8% of children and adolescents received influenza vaccination, which improved modestly during the study period compared with the prior influenza season ( P = .009). Actual adherence to recommendations, including dosing, timeliness, and avoidance of missed opportunities, was 46.4% of patients cared for by the PRACTICE. The WBT was most effective in promoting adherence with vaccination recommendations with an estimated average odds ratio = 1.26, P < .05, to compare between preintervention and intervention periods. Over the influenza season, there was a significantly increasing trend in odds ratio in the WBT arm ( P < .05). Encouraging process improvements and providing longitudinal feedback on monthly rate of vaccination sparked some practice changes but limited impact on outcomes. Conclusions: Web-based training at the start of influenza season with monthly reports of adherence can improve correct dose and timing of influenza vaccination with modest impact on overall vaccination rate.